Smart off-line webinar for distant education - Peter Schmidt; Ján Pittner (Открытое образование (Москва))
The article is devoted to searching the ways of effective development of modern electronic courses using smart presentations in teaching net technologies for university students considering difference in students’ input knowledge and their initial level.